Comparative analysis on the effects of weathering on construction materials used for temporary shelter envelope - Leobrera, Karen Joy R.
Considering the highly variable weather conditions in the Philippines, need arises to determine the best-suited material for a temporary shelter envelope that could withstand weathering for a long period of time. Polycarbonate and polyvinyl chloride panels are two of the proposed materials. They are subjected to an accelerated weathering test using a QUV accelerated weathering apparatus equipped with UVA 340 nm lamps. The materials are weathered for 2000 hours and every 500 hours, groups of samples are subjected to color evaluation, flexural strength test and flammability test. The results of the study shows that polycarbonate's yellowing becomes more pronounced as time progresses while polyvinyl chloride experiences initial whitening before it starts yellowing. The experimental results under flexural strength test shows that the modulus of elasticity for polycarbonate increases by almost 24% even after 1000 hours of weathering and by 4% after 2000 hours. PVC also experiences the same increase in modulus but only up to 5%. The increase is the effect of cross linking of the molecules. Cross-linking increases the molecular weight of the polymer as well as the bonding between polymer chains. This reduces the molecular mobility of the molecules and increases the material's strength. No linear burning rate is recorded for both samples under flammability test since after removing the flame, the samples stop burning. This means that the flame retardant properties of both materials are still in effect even after 2000 hours of weathering.